Rhabdomyosarcoma in a pediatric patient: A rare case report - S P Shrutha; G B Vinit (Wolters Kluwer Medknow Publications, 2015)
Rhabdomyosarcoma (RMS), a tumor of skeletal muscle origin, is the second most common soft tissue sarcoma encountered in childhood after osteosarcoma. The common sites of occurrence are the head and neck region, genitourinary tract, retroperitoneum, and to a lesser extent, the extremities. Site predilections in the oral cavity are a soft palate, maxillary sinus and alveolus, posterior mandibular region, cheek and lip, and possibly tongue. RMS is a highly malignant tumor with extensive local invasions and early hemorrhagic and lymphatic dissemination. Despite aggressive approaches incorporating surgery, dose-intensive combination chemotherapy, and radiation therapy, the outcome for patients with metastatic disease remains poor. Here, we report a case of oral RMS in a 1-year-old child and describe the clinical, radiological, histopathological, and immunohistochemical findings.